Good Corporate Governance Analysis of the Performance of Maqashid Sharia Bank Muamalat Indonesia - Ahmad, Fikri Abdulloh; Yandri, Pitri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Measuring the performance of Sharia banking using financial ratios that are currently frequently used, such as ROA, ROE, CAMELS, and so on, is considered unable to describe the true value of Sharia banking. Muhammad, Razak, and Taib developed sharia bank performance measurement based on Abu Zahra's maqashid sharia concept with 3 main objectives, namely tahdzîb alfardi (educating people), iqâmah al-'adl (upholding justice), and jalb al-maslahah (public interest) which later called the Maqashid Syaria Index (MSI). In achieving good maqashid sharia values, of course, good corporate governance is needed. The board of directors, commissioners and also the sharia supervisory board are considered to have an important role in the supervision and direction of sharia bank policy, so they become the main instruments in implementing Good Corporate Governance (GCG). This research examines the influence of internal ownership of directors and commissioners, tenure of directors and commissioners, concurrent DPS positions, and DPS expertise on the performance of Bank Muamalat Indonesia's MSI using panel data regression. The results of this research show that the internal ownership of commissioners, the terms of office of directors and commissioners influence the MSI of Bank Muamalat Indonesia, while the internal ownership of directors, DPS expertise, and dual DPS positions do not influence the MSI of Bank Muamalat Indonesia.